2023
DOI: 10.3390/agriculture13061228
|View full text |Cite
|
Sign up to set email alerts
|

Air Frosts in Poland in the Thermal Growing Season (AT > 5 °C)

Abstract: Frosts cause damage to plants in field crops and also trees, thus contributing to heavy economic losses in agriculture. One of the consequences of climate warming is the lengthening of the thermal growing season (AT > 5 °C) and acceleration of phenological phases as well as the lengthening of the frost-free period. This favourable element allows the extension of the range of cultivated plants to include plants requiring warmth and a longer development period. The present study concerns the area of Poland. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Szyga-Pluta et al [29] found an increase in the length of the growing season in Poland by an average of 4.8 days over 10 years between 1966 and 2020. A slightly higher rate of the said changes, on average by 6.2 days over the period of 10 years, however, for another multiannual period (1971-2020), was determined by Koźmi ński et al [4]. In the thermal growing season (air temperature > 5 °C), the average number of days with ground frosts in Poland amounts to 28 and ranges in spring from 10 to 26, and in autumn from 6 to 16 (Figure 2).…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…Szyga-Pluta et al [29] found an increase in the length of the growing season in Poland by an average of 4.8 days over 10 years between 1966 and 2020. A slightly higher rate of the said changes, on average by 6.2 days over the period of 10 years, however, for another multiannual period (1971-2020), was determined by Koźmi ński et al [4]. In the thermal growing season (air temperature > 5 °C), the average number of days with ground frosts in Poland amounts to 28 and ranges in spring from 10 to 26, and in autumn from 6 to 16 (Figure 2).…”
Section: Resultsmentioning
confidence: 79%
“…It is noteworthy that there is a marked, statistically significant trend of an earlier ending date of the last spring frosts and increasingly later occurrence in autumn which, in turn, results in the lengthening of the frost-free period. Multiannual variability of the aforementioned characteristics, both local as well as throughout the country, was confirmed by numerous authors [3,4,11,[16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations